Reconciling the definitions of raw meat-based diets and biologically appropriate raw foods for companion animals: a mini review - Kiprotich, Samuel S.; Altom, Eric; Mason, Robert; Aldrich, Charles G. (Frontiers in Veterinary Science, 2025)
There is an increasing demand for pet foods considered “natural,” raw, uncooked, minimally processed, and those free of synthetic preservatives used to inactivate spoilage and pathogenic microorganisms. These diets are referred to as raw meat-based diets (RMBDs), biologically appropriate raw foods (BARFs) or raw animal products (RAPs). However, the definitions of these diets are highly subjective and rely on the interpretation of pet food manufacturers, researchers, consumers, and animal food regulatory authorities. The lack of standardized definitions hampers the necessary progress in research required to better understand this rapidly growing segment of pet food. The different definitions reduce the efficiency of international and interstate commerce between pet food manufacturers, ingredient suppliers, consumers and the regulatory authorities in different geographical jurisdictions. There is a plethora of existing literature defining and describing what raw pet foods are. Thus, a comprehensive search for published research was conducted regarding definitions and word descriptions tangential to these raw pet foods. This mini review paper explored multiple research and review articles that attempted to define “raw pet foods,” and the word descriptions they used. This review focuses on RMBDs, BARFs, “raw pet foods,” and RAPs as defined from an academic, processing, regulatory and consumer perspective. Furthermore, we have proposed a new working definition for these diets as “Raw and Minimally Processed” (RAMP) pet food to reflect consumer, regulatory and academic needs, and expectations. Reconciling these definitions will lay a better framework for communication, research, regulation, and commerce between stakeholders in the pet food industry.